Komparasi Sistem Pemilihan Umum Estonia - Indonesia : Penerapan I-Voting - Munawaroh, Umi Rofiatun (Fakultas Syariah Institut Agama Islam Negeri Palu, 2023)
This article discusses a comparison of the electoral systems that tahe place in Indonesian and Estonia. Estonia is a country that implements Parlianmentary democracy while Indonesian is a country that implements Pancasila Democracy. Estonia is a republic with a president as head of state and a prime minister as head of goverment. Indonesian has the same form of state as Estonia, namely a republic. However, Indonesian does not adhere to a parlianmentary system which is reflected in the president’s position as head of government who is assisted in carrying out his duties by the vice presdient. Estonia is considered a developed country because it has an all-electronic government system or can be accessed via the internet. This has been implemented in an election system called e-voting since 2005. Until now, Indonesia still uses the conventional voting system through ballots. Many problems arise in the conventional electoral system through ballots considering Indonesia’s vast territory and difficulties in accessing election logistics. Therefore, a discussion on the comparison of the two countries in the general electoral system is to find out the similarities and differences in the system applied. The method used in this research is a literature study using a comparative approach. The method used in this research is a literature study using a comparative approach. The research method uses literature study by quoting data from websites, journals and books that discuss the general election system in Indonesia and Estonia. The results of this research are a comparison of the electoral system of Indonesia and Estonia. It is especially important for Indonesia to be able to modify Estonia’s general election system which is considered very modern because it uses Internet Voting.